EFFECTS OF CAFFEINE IN FEMALE RAT MODELS OF DEPRESSION - Mizin Валерія; Severynovska Олена (Biota. Human. Technology, 2025)
Purpose of the research. Assessment of the effect of caffeine on behavioral indicators of female rats in a state of depression induced by methods of unpredictable stress and contagious depression. Methodology. The study was conducted on white sexually mature female rats weighing 230–300 g (N = 72), divided into six groups: intact; females with depression (method of unpredictable chronic stress); female rats that were given caffeine via gavage at a concentration of 25 mg/kg for 5 weeks; females with depression that were given caffeine; female rats with contagious depression; female rats with contagious depression that were given caffeine. Two validated methods were used to assess depressive behavior: the sucrose preference test and the forced swim test. The sucrose preference test was used to determine anhedonia. The forced swim test evaluated immobilization and climbing to assess helpless behavior and stress adaptation activity. Data were analyzed using a two-way analysis of variance (ANOVA) with Tukey’s post hoc test. Scientific novelty. For the first time, a comparative study of the effect of caffeine on female rats in two different models of depression was conducted. The results obtained allowed us to evaluate different mechanisms of depressive behavior caused by chronic stress and social factors. The analysis allowed us to determine that the effectiveness of caffeine varies depending on the type of depression. Conclusions. In female rats in models of unpredictable stress and contagious depression, manifestations of anhedonia were observed, namely, a decrease in sucrose preference compared to the control group. An increase in immobility time and a decrease in climbing were also observed, which indicates the formation of helpless behavior. This shows different neurobiological mechanisms of stress regulation depending on its nature. Caffeine had a pronounced antidepressant effect depending on the model of depression. In females in the model of chronic unpredictable stress, caffeine caused an increase in sucrose preference, a decrease in immobilization time, and an increase in climbing. Still, these indicators remained lower than control values. In females with contagious depression, the effect of caffeine was more pronounced: indicators of sucrose preference and climbing almost reached control values. This may be due to the impact of caffeine on social and emotional aspects of behavior. At the same time, in chronic stress, where changes affect more complex adaptation mechanisms, its effect is less pronounced.